The Effect of Online-Based Transportation on Conventional Transportation Revenues in Baubau City - Agusman Agusman; Hendra Kundrad Susanto; Muh. Indriyan (Civil Engineering Faculty, Universitas Muhammadiyah Buton, 2021)
Online-based transportation is a type of transportation that uses a smartphone to store applications in the form of a server that can be used to order transportation equipment in the form of two-wheeled or four-wheeled vehicles. With this online transportation, consumers now no longer have to wait or have to go to wait at the motorcycle taxi stand or at the roadside to wait for a taxi or tell the address because Taxi online already has a coordinate point for a pick-up point for customers. It can even be picked up at home though. In addition, consumers do not need to haggle about fares, because they have been determined based on the distance traveled. Initially, the presence of conventional taxis (Ade Taksi) in Baubau City was 25 units, but over time and coupled with the presence of online transportation, now there are only 8 taxi units that are actively operating. The purpose of this study is to find out how much influence the existence of online-based transportation has on the income of conventional taxi drivers and how people are interested in using conventional taxis after online transportation. Based on the results of research, online transportation has a very negative influence on the income or income of conventional taxi drivers. As evidence, it can be seen from the results of the study that the income of taxi drivers decreased before the presence of online transportation and after the presence of online transportation. The average income earned by conventional taxi drivers is Rp. 4,312,500 and after online transportation of Rp. 3,412,500 and the presence of online-based transportation has a negative impact on the large number of interest in using conventional taxis. This can be proven by the decrease in monthly taxi revenue before the online-based transportation and after the online-based transportation. So that the average number of taxi enthusiasts or customers before the online online-based transportation was 1,170 calls and the average number of customers after the online-based transportation was 927 calls (10.9%). 500 and the presence of online-based transportation has a negative impact on the large number of interest in using conventional taxis. This can be proven by the decrease in monthly taxi revenue before the online-based transportation and after the online-based transportation. So that the average number of taxi enthusiasts or customers before the online online-based transportation was 1,170 calls and the average number of customers after the online-based transportation was 927 calls (10.9%). 500 and the presence of online-based transportation has a negative impact on the large number of interest in using conventional taxis. This can be proven by the decrease in monthly taxi revenue before the online-based transportation and after the online-based transportation. So that the average number of taxi enthusiasts or customers before the online online-based transportation was 1,170 calls and the average number of customers after the online-based transportation was 927 calls (10.9%).